2009
DOI: 10.1016/j.healun.2009.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Prior Human Leukocyte Antigen-Allosensitization and Left Ventricular Assist Device Type Affect Degree of Post-implantation Human Leukocyte Antigen-Allosensitization

Abstract: Background Temporary use of left ventricular assist devices (LVADs) prior to heart transplantation has been associated with formation of antibodies directed against human leukocyte antigens (HLA), often referred to as sensitization. Identifying specific factors that might predispose patients to form HLA-specific antibodies after LVAD implantation may facilitate the development of strategies to prevent high degree of sensitization. We investigated whether prior sensitization or LVAD type affected the degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 24 publications
2
42
0
Order By: Relevance
“…14,[17][18][19] Using the OPTN adult data, Arnaoutakis et al 14 demonstrated that device type (continuous flow versus pulsatile, with higher sensitization rates in latter) or levels of panel-reactive antibody activity (>25% defined as high) were not associated with worse mortality. Furthermore, they found that panel-reactive antibody activity did not affect rejection rates in the first year after transplant.…”
mentioning
confidence: 99%
“…14,[17][18][19] Using the OPTN adult data, Arnaoutakis et al 14 demonstrated that device type (continuous flow versus pulsatile, with higher sensitization rates in latter) or levels of panel-reactive antibody activity (>25% defined as high) were not associated with worse mortality. Furthermore, they found that panel-reactive antibody activity did not affect rejection rates in the first year after transplant.…”
mentioning
confidence: 99%
“…Drakos [13] undertook a study to determine risk factors contributing to allosensitization. They reviewed records of 75 patients, most of whom received the HeartMate I.…”
Section: Volume Displacement Pumpsmentioning
confidence: 99%